HUBUNGAN STATUS GIZI TERHADAP USIA MENARCHE SISWI MADRASAH IBTIDAIYAH MUHAMMADIYAH KISMOYOSO NGEMPLAK BOYOLALI - Retno Dewi Noviyanti; Sri Mintarsih; Sansavera Nur Fatimah (KOSALA : Jurnal Ilmu Kesehatan, 2016)
Background : Menarche is the first period that is common in the age range 10-16years or in early adolescence middle of puberty before entering the reproductiveperiod. Research of Aishah (2011) concluded that female students who havehigher nutritional status (BMI) will get menarche faster. Likes research of Mundaet al (2012) concluded that female students with overweight get menarche fasterthan female students with normal and underweight category.Methods : This research used a deskriptif kuantitatif, retrospective studyapproach. This research was conducted in Madrasah Ibtidaiyah MuhammadiyahKismoyoso Ngemplak Boyolali. Research subjects were used female students ofelementary school in grade V and VI, with total sampling metode consist of 15students who had experienced menarche. The data of the research wereanalyzed by using Pearson Product Moment formula. This formula used toanalysis the relationship between nutritional status with the age of menarche offemale students of Madrasah Ibtidaiyah Muhammadiyah Kismoyoso NgemplakBoyolali.Result and Conclusion : The average of nutritional status based on percentageof Weight for Age was -87,9 Â± 14,2, normal category 73.3 %, middle category20% and underweight 6.7 %. The average of the age of menarche of femalestudents was 141.7 Â± 10.7 month, with normal category age of menarche 100 %.The results of Pearson Product Moment test was p = 0.104.Based on the results of the research can be concluded that there was norelationship between the nutritional status with the age of menarche of femalestudents of Madrasah Ibtidaiyah Muhammadiyah Kismoyoso Ngemplak Boyolali.Keywords: female students of elementary school, menarche, nutritional status.